Gerenciamento da impressão da legitimidade nas universidades federais - Pontelli, Greice Eccel (2019)
The acts of federal universities become transparent to comply with the legality principle but rarely disclose any supplementary information. The management reports (MR) are the main channel of transparency and reduction of asymmetry of information between Federal Universities and their stakeholders. This research explores institutional and organizational legitimation based on the inspectional aspects described along 189 MR from 2014 to 2016. Document analysis of the evidence of RG revealed 14 variables of binary and discrete data, as well as qualitative data to measure the integrity MR data matching it with CGU-PAD system (Central Government Internal Auditing Office) data. The data analysis splits Universities into three clusters. The first one is set according to processes concentration, the second to evidence characteristics and the third to procedural efficiency. These clusters revealed isomorphism except for some differences in integrity of suspensions penalties disclosure, as well as, in degree of detailing processes besides further detaling in Universities internal inspectional units. Evidence of legitimacy management was identified in a manner consistent with the literature through the analysis of correspondence between the groupings of efficiency and evidences characteristics of reporting. Keywords: Legitimacy. Disclosure. Public Universities. Inspection.